MODEL MODEL PEMBELAJARAN GERAK DASAR LONCAT MELALUI PERMAINAN LONCAT KATAK BAGI SISWA KELAS V SD NEGERI KADENGAN 02 KECAMATAN RANDUBLATUNG KABUPATEN BLORA TAHUN2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Jump basic motion game is still taught in the form of a standard game thus obtained is still less activestudents in learning basic movement jump, students still feel bored and delivery of content that is lessattractive to students. This research method is the development of research, and the results of the model ofdevelopment of game developers jump rope. The analysis procedure includes product development productthat will be developed, developing initial products, expert validation and revision, testing and revisionsmall group, large group and test the final product. The data was collected using field observations andquestionnaires were obtained from expert evaluation and the results of the questionnaires by students. Thedata analysis technique used is descriptive percentages. From the test results obtained by the expertevaluation data, expert Penjasorkes 85.3% (good), learning experts I 88% (good), a learning II 85.3%(good). Data is being a small-scale trial results psychomotor aspects of the observations of 73.2% (good),cognitive aspects of the questionnaire 85% (good), affective aspects of the questionnaire 84% (good) andlarge-scale trials observational aspects of psychomotor 76.6% (both ), cognitive aspects of thequestionnaire 87.9% (good), affective 85.3% (good). Based on the research data, it was concluded that thejump rope game can be used by teachers penjas as an alternative in learning Penjasorkes game.